2014
DOI: 10.1088/0031-9155/59/8/1899
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional high spatial-resolution dosimeter using europium doped potassium chloride: a feasibility study

Abstract: Recent research has shown that KCl:Eu2+ has great potential for use in megavoltage radiation therapy dosimetry because this material exhibits excellent storage performance and is reusable due to strong radiation hardness. This work reports the authors’ attempts to fabricate 2D KCl:Eu2+ storage phosphor films (SPFs) using both a physical vapor deposition (PVD) method and a tape casting method. X ray diffraction analysis showed that a 10 µm thick PVD sample was composed of highly crystalline KCl. No additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…6(d) indicates that the KCl:Sm nanophosphor may be a good sensitive material for radiation dosimetry. 13 The dose response for beta irradiation also yielded a linear correlation coefficient r ¼ 0.91 for doses up to 3 Gy [ Fig. 6(b)].…”
Section: Osl Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…6(d) indicates that the KCl:Sm nanophosphor may be a good sensitive material for radiation dosimetry. 13 The dose response for beta irradiation also yielded a linear correlation coefficient r ¼ 0.91 for doses up to 3 Gy [ Fig. 6(b)].…”
Section: Osl Measurementsmentioning
confidence: 98%
“…However, these materials have a high Z eff (49) and show undesirable strong photon energy dependence. 13 KBr:Eu and KCl:Eu do not show any photon energy dependence and also exhibit less fading in the dark at room temperature. 14 On the other hand, the low-cost halide material KCl, which is abundantly found in nature, has a lower effective atomic number than that of other storage phosphors such as BaFBr, KBr, etc., making it more suitable for radiation dosimetry.…”
Section: Introductionmentioning
confidence: 96%
“…The choice of the desired computational method directly affects the precision of results; nevertheless, this precision must be evaluated considering computational costs and the size of system in study. [26][27][28][29][30][31][32][33][34] In this contribution, we studied the photoluminescence of MEH-PPV in solution prepared in a variety of good and non-solvents, as well as thin films and solid solutions. Steady-state and time-resolved fluorescence spectroscopy were used to determine the total photoluminescence as a sum of contributions from several fluorescent moieties present in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work (Li et al, 2014) has shown that KCl:Eu 2+ has great potential for use in megavoltage radiation therapy dosimetry because this material exhibits excellent storage performance and is reusable due to strong radiation hardness. Hansel et al (Hansel et al, 2014) report that KCl:Eu 2+ samples provide excellent signal even after they were given doses of up to 200 kGy at the Louisiana State University Synchrotron facility.…”
Section: Introductionmentioning
confidence: 99%